Do premolar extractions necessarily result in a flat face? No, when properly indicated - Susiane Allgayer; Maurício Barbieri Mezomo
Abstract The esthetic benefits are among the main goals of orthodontic treatment; therefore, tooth extractions have been avoided as a protocol for orthodontic treatment because they may impair the facial profile. The present article discusses aspects as the magnitude and response of soft tissue profile due to changes in incisor positioning, and the effect of different sequences of premolar extraction. One case report illustrates the subject, with favorable and stable esthetic and occlusal outcomes five years after orthodontic treatment with extraction of second premolars.